Services and Targets of Anjuman-i Taraqqi-i Urdu: An Overview - Ahamad, Nazir; Tariq, Gulshan (sourcecoder, 2022)
This article aims to present an overview of the services and targets of Anjuman-i Taraqqi-i Urdu. For this purpose, library based approach has been adopted to collect the material from different sources e.g. Urdu journal, and other books published about the Anjuman-i Taraqqi-i Urdu from time-to-time. The material (obtained from different sources) has been critically reviewed. As a result, Anjuman-i Taraqqi-i Urdu has been found to focus on different target related with the development of Urdu language e.g. promotion and dissemination of Urdu, publication of critical literature, and continuous publication of the Urdu journal, and resumption of the publication of classical Urdu texts. Anjuman-i Taraqqi-i Urdu has been found successful in achieving the targets related with the publication of classical, and critical texts. However, it has been found unsuccessful to achieve the targets related with the promotion and dissemination of Urdu language, and the continuous publication of the Urdu journal because of a number of factors e.g. lack of sufficient funds, and internal conspiracies. These findings lead to conclude that Anjuman-i Taraqqi-i Urdu rendered useful services however it remained partially successful in the achievement of its targets. Therefore, Anjuman-i Taraqqi-i Urdu is proposed to increase its funds, and appoint sincere team members like Malvi Abdul Haq, Jamil-ud-Din Aali, Mushfiq Khawaja and Akhtar Hussain for the successful achievement of its targets